Genome-wide identification and characterization of the stress-associated proteins (SAPs) gene family in Amaranthus palmeri S. Watson - Binbin Liu; Youning Wang; Lu Cai; Zhouxingyu Wang; Fulian Wang; Wang Chen; Dongfang Ma (Molecular Biology Reports, 2026)

Ustiloxins induce kidney injury via the TLR2/MAPK/NF-κB pathway - Yingchun Du; Guomei Zhang; Xuming Zhou; Youning Ma; Zhaoyun Cao; Ying Yu; Lihua Sun (Toxicon, 2025)

Full-length transcriptomics study of Ustiloxins-induced hepatocyte injury - Guomei Zhang; Xuming Zhou; Shanshan Liu; Youning Ma; Han Li; Yingchun Du; Zhaoyun Cao; Lihua Sun (Toxicon, 2024)

Transcriptomic Signatures of Pearl Oyster Pinctada Maxima in Response to Acute Salinity Stress - Haijun Wei; Mingqiang Chen; Zhenghua Deng; Jing Sun; Jingru Yang; Wang Zhao; Youning Li; Zhenhua Ma; Yu Wang; Gang Yu (Frontiers in Marine Science, 2022)
Acute salinity stress can impact many physiological processes of marine shellfish. The responses of Pinctada maxima to salinity stress, especially the osmotic pressure regulation and immune response, are of great significance to health. To investigate the molecular changes in response to acute salinity stress, the pearl oysters were transferred from 30 ppt (C) to 40 ppt (HS) and 20 ppt (LS) for 12 h, and the transcriptome analysis was conducted on the gills. Compared to the control, there were 6613 (3253 up-regulated and 3360 down-regulated) differentially expressed genes (DEGs), 4395 (2180 up-regulated and 2215 down-regulated) DEGs observed in HS and LS, respectively. The related molecular biological processes and potential functions were explored from enrichment analysis. A total of 332 KEGG pathways (including 1514 genes) and 308 KEGG pathways (including 731 genes) were enriched in C vs. HS and C vs. LS, respectively. In addition, there are 1559 DEGs shared by C vs. HS group and C vs. LS group, and the results of the KEGG function annotation showed that 7 DEGs were involved in membrane transport, and 34 DEGs were involved in the immune system. The correlation network for expression of genes shows that the expression of 3 genes was significantly correlated with each other in membrane transport, and there were significant correlations between the expression of 27 genes in immune response. The results of this study will be of great value in understanding the molecular basis of salinity stress adaptation in the pearl oyster P. maxima .

Effects of prey color, wall color and water color on food ingestion of larval orange-spotted grouper Epinephelus coioides (Hamilton, 1822) - Jiasong Zhang; Huayang Guo; Zhenhua Ma; Shigui Jiang; Kaichang Wu; Youning Li; Jian G. Qin (Aquaculture International, 2015)

Molecular characterization and expression analysis of lipopolysaccharide and β-1,3-glucan-binding protein (LGBP) from pearl oyster Pinctada fucata - Dianchang Zhang; Jianjun Ma; Jingjing Jiang; Lihua Qiu; Caiyan Zhu; Tianfeng Su; Youning Li; Kaichang Wu; Shigui Jiang (Molecular Biology Reports, 2010)